Students' Attitudes on Electronic English Learning - Yosieka Maharani; Dedi Rahman Nur (Borneo Educational Journal (Borju), 2021)
Along with the development of technology in various aspects of life, technology has a significant impact and influence in today's life. One of the roles of technology in learning activities is to support the learning activities more manageable to accomplish and exciting in the educational sector. One of the developments of technology in the education sector is E-Learning. E-Learning may be an option to be used in class as a learning tool. Especially on English subject when some students may find it difficult, E-Learning could be their alternative to learn English the significance of this study to find out the students' perspective regarding E-Learning in English. The data will be conducted by distributing a questionnaire to students. The objectives of this study are to find out attitudes from students toward E-Learning. The study was conducted in Bunga Bangsa Islamic Junior High School involving 56 students. A questionnaire was used as an instrument to collect the data, which score analyzed based on the mean score. The result showed students have positive attitudes toward E-Learning. In terms of students' attitudes, it is found that students have positive attitudes toward E-Learning since they found E-Learning is appropriate to use, effective, and excellent technique to help them learn English.